In Situ Back‐Contact Passivation Improves Photovoltage and Fill Factor in Perovskite Solar Cells. Issue 14 (10th February 2019) - Tan, Furui; Tan, Hairen; Saidaminov, Makhsud I.; Wei, Mingyang; Liu, Mengxia; Mei, Anyi; Li, Peicheng; Zhang, Bowen; Tan, Chih‐Shan; Gong, Xiwen; Zhao, Yongbiao; Kirmani, Ahmad R.; et al.
Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) have seen a rapid rise in power conversion efficiencies in recent years; however, they still suffer from interfacial recombination and charge extraction losses at interfaces between the perovskite absorber and the charge–transport layers. Here, in situ back‐contact passivation (BCP) that reduces interfacial and extraction losses between the perovskite absorber and the hole transport layer (HTL) is reported. A thin layer of nondoped semiconducting polymer at the perovskite/HTL interface is introduced and it is shown that the use of the semiconductor polymer permits—in contrast with previously studied insulator‐based passivants—the use of a relatively thick passivating layer. It is shown that a flat‐band alignment between the perovskite and polymer passivation layers achieves a high photovoltage and fill factor: the resultant BCP enables a photovoltage of 1.15 V and a fill factor of 83% in 1.53 eV bandgap PSCs, leading to an efficiency of 21.6% in planar solar cells. Abstract : An in situ back‐contact passivation strategy is adopted to optimize the photovoltaic performance of n–i–p planar perovskite solar cells. Devices with a flat‐band alignment between the perovskite and polymer passivation layer achieve a high photovoltage of 1.15 V and fill factor of 83% with 1.53 eV bandgap perovskite, leading to a stabilized power conversion efficiency of 21.6%.